2021
DOI: 10.1002/anie.202016122
|View full text |Cite
|
Sign up to set email alerts
|

A Macromolecular Drug for Cancer Therapy via Extracellular Calcification

Abstract: Cancer chemotherapy typically relies on drug endocytosis and inhibits tumor cell proliferation via intracellular pathways; however, severe side effects may arise. In this study, we performed a first attempt to develop macromolecular‐induced extracellular chemotherapy involving biomineralization by absorbing calcium from the blood through a new type of drug, polysialic acid conjugated with folate (folate‐polySia), which selectively induces biogenic mineral formation on tumor cells and results in the pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…As shown in Figure 1D and Figure S7, Supporting Information, the green fluorescence of the biomineral layer stained by calcein co‐localized with the red fluorescence of cancer cell membrane in the DPA and DPAC groups. [ 13 ] In sharp contrast, there was no apparent green fluorescence in the Control or Ca group. To further confirm the deposition of Ca, we observed 143B cells in different groups through scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure 1D and Figure S7, Supporting Information, the green fluorescence of the biomineral layer stained by calcein co‐localized with the red fluorescence of cancer cell membrane in the DPA and DPAC groups. [ 13 ] In sharp contrast, there was no apparent green fluorescence in the Control or Ca group. To further confirm the deposition of Ca, we observed 143B cells in different groups through scanning electron microscopy (SEM).…”
Section: Resultsmentioning
confidence: 97%
“…These observations imply that calcification of a tumor may have a positive effect on the inhibition of tumor cell proliferation, resulting in a therapeutic effect on tumors. Inspired by this, we proposed a cancer-cell-targeting calcification strategy and achieved tumor calcification spontaneously to inhibit tumor growth and metastasis induced by polycarboxylic macromolecules, , which is similar to the formation of hard tissue in living bodies, such as the physiological formation of bone and teeth. However, our pilot study implied that artificial tumor calcification showed limited tumor-inhibiting ability, as the speed of calcification is quite low, , which also impairs the ability of tumor calcification to prevent tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this, we proposed a cancer-cell-targeting calcification strategy and achieved tumor calcification spontaneously to inhibit tumor growth and metastasis induced by polycarboxylic macromolecules, , which is similar to the formation of hard tissue in living bodies, such as the physiological formation of bone and teeth. However, our pilot study implied that artificial tumor calcification showed limited tumor-inhibiting ability, as the speed of calcification is quite low, , which also impairs the ability of tumor calcification to prevent tumor metastasis. Moreover, the slow calcification process cannot induce effective tumor calcification points for medical imaging in a relatively short time, which also limits its effectiveness of tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[60] Excessive Ca 2+ can cause extracellular calcification that causes cancer cell death. [61] We also explored the effect of Ca 2+ on the proliferation, invasion, and migration of HCC cells in vitro via colony formation assay, transwell assay, and wound healing assay. The results were displayed in Figure S2 in the Supporting Information.…”
Section: Changes Of Tumor Cytokines After Taementioning
confidence: 99%